Contexto institucional da governança nas universidades federais do nordeste brasileiro - Farias, Mylena Soares de Araújo (2020)
Based on a survey by the Federal Court of Accounts (TCU) pointing to a deficit scenario in the governance panorama in Public Institutions of Higher Education in 2015, and considering the publication of legal marks on the theme by the Presidency of the Republic, Public Ministry, Controllership-General of the Union and Federal Court of Accounts in later years, this thesis has as its general objective to present an overview of current Governance in federal universities in Northeast Brazil, and as specific objectives to understand the origin of the term Governance, to present the history of higher education in Brazil and delimit variables for the construction of an instrument to verify the current Governance panorama in Brazilian federal universities. The study's problem is: “What is the current scenario of federal universities in Northeast Brazil from the perspective of Governance?” and the methodology adopted was exploratory, descriptive, explanatory and documentary. The sample consisted of 9 federal universities, each representing a state in the Northeast of Brazil, and the documents of these institutions in force at the time of publication of this study were considered. The governance principles that stand out for appearing repeatedly in the legal papers from the official agencies mentioned above were then organized into four areas, namely: 1. Leadership; 2. Integrity; 3. Accountability and; 4. Strategic alignment. We then classified within these areas the criteria based on the other principles found in the documents considered in the study for the preparation of the instrument that was used to verify the panorama of universities from the perspective of Governance. Considering the recent dates of publication of legal marks, the hypothesis tested was that federal universities in Northeast Brazil have not yet defined their Governance processes in a clear and publicized way. The hypothesis was proven with the finding that the universities considered do not present positive results in most areas that make up the assessment instrument, standing out only in area 3. Accountability, where the accountability and accountability of senior management were verified through publication of administrative accountability for the management and existence of an Ombudsman at Universities and/or association with the e-OUV System.